2014
DOI: 10.24846/v23i2y201403
|View full text |Cite
|
Sign up to set email alerts
|

Bounded Confidence-based Opinion Formation for Opinion Leaders and Opinion Followers on Social Networks

Abstract: Opinion dynamics is a complex collective behavior in human societies. When individuals exchange opinions with others, they usually adopt a bounded confidence rule and only accept the opinions within the confidence range. Furthermore, individuals are heterogeneous in real social systems. Thus, they have distinct confidence levels, and also play different roles in the collective opinion formation. In this paper, a leader-follower bounded confidence model is proposed for a group of social agents, who have heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…5 show that increasing the appeal of both the leaders makes it easier for the normal agents to achieve consensus (i.e. it lowers the consensus threshold), which confirms the findings in 21 , because they are more likely to be influenced by both leaders which makes them achieve consensus roughly at the average opinion of the leaders. There is a common pattern for most of the appeal values in Fig.…”
Section: Impact Of Stubbornness On Opinion Dynamicssupporting
confidence: 75%
See 1 more Smart Citation
“…5 show that increasing the appeal of both the leaders makes it easier for the normal agents to achieve consensus (i.e. it lowers the consensus threshold), which confirms the findings in 21 , because they are more likely to be influenced by both leaders which makes them achieve consensus roughly at the average opinion of the leaders. There is a common pattern for most of the appeal values in Fig.…”
Section: Impact Of Stubbornness On Opinion Dynamicssupporting
confidence: 75%
“…It was also suggested 17 that opinion leaders should maintain invariable opinions in the process of opinion dynamics, which is sometimes called stubbornness 19,20 . More recently, Zhao and Kou 21 proposed an opinion leader-follower model which divides the whole group into two sub-groups, i.e., a leader sub-group and a follower sub-group, and the information / influence transition is based on the principle of a two-step flow model where the opinion update is based on a bounded confidence model, the Hegselmann-Krause (HK) model 22,23 . Their results showed that the opinion followers are strongly influenced by the leaders if they have higher confidence levels and trust degrees in the leaders.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that most studies indicated that opinion leaders played an important role in information propagation. In many cases, opinion leaders may transfer the information to the neighboring agents unconsciously [48]. However, in some NIMBY conflict cases, opinion leaders hoped to guide the neighbors to an expected opinion for a purpose, such as panic boycott.…”
Section: Related Workmentioning
confidence: 99%
“…The group scale has a significant impact on the activity as one of elements of collective behavior in 52 mass incidents occurred in China during 2007-2011 [55], as well as collective opinion evolution [48]; these can show that formation and evolution of any public opinion need a considerable number of participants. Meanwhile, the average scale of these 52 mass incidents was within the interval [100, 900], so in our simulation the size of the considered network is selected as n = 500.…”
Section: Parameter Interpretationmentioning
confidence: 99%
“…Meanwhile, the concept of opinion leadership can be used to categorize social media users into two groups: opinion leaders and opinion followers [14]. The former commands a greater fan following, and is more popular in the online community than the latter.…”
Section: Introductionmentioning
confidence: 99%